Effect of muscle active force and fiber orientation on the left ventricle mechanics of human heart - Hassan, M.A.; Sarhan, A.A.D.; Amano, A. (2011)
in this paper, the effects of muscle active force and fiber orientation of the heart cells on the left ventricle ejection volume, wall thickening and stress distributions have been studied by finite element method (FEM). Three-dimensional left ventricle (LV) geometrical model was reconstructed from 65 transverse MRI tagging of a healthy human heart at the end of the diastole. Different muscle/fiber orientations were studied whereas muscle-active forces were directed along muscle fibers. Simulation results were very sensitive to the fiber orientation angles and the magnitude of the active force generated by LV-muscles during the isometric contraction and ejection phases. It was found that large magnitudes of active force almost lead to early start of contraction and delayed relaxation over one heart period. Mechanical response of the LV not only relies on the passive material resistance of the tissues but it mainly relies on the magnitude and direction of the muscle active force.